Relation between the shear stress distribution and the resulting acoustic emission variation in concrete beams. Issue 6 (11th February 2020) - Liu, Simeng; Wu, Caixing; Zhou, Jianting; Liu, Tenfei; Zhuang, Shaoqi; Luo, Yulin; Yang, Xu
Summary: Acoustic emission (AE) technology is extensively acknowledged as a promising structural health monitoring (SHM) approach; meanwhile, AE monitoring has long been criticised for a lack of quantitative results. This work revealed a strong correlation between the shear stress distribution and the resulting AE distribution, enabling accurate and real‐time quantification of the shear stress states in concrete beams using only AE measurements. This paper started by introducing the AE phenomenon and the theoretical distribution of the shear stresses on a beam cross section, which revealed that the distributions of the stresses and the resulting emissions inherently correlate to each other. Twelve reinforced concrete beams were then tested, deploying devices including an AE system. The results showed that the AE source intensity distribution strongly correlated with that of the shear stresses in a beam segment when the beam was in both the working stage and the failure phase and that the matching degree of these two distribution curves varied from 79.20% to 94.12%. The correlation revealed in the paper will boost a wide range of significant AE‐based scientific research and engineering applications, including SHM and non‐destructive testing.